The Role of Non-Whites in the South African Defence Force - Nöthling, C.J.; Steyn, L. (Scientia Militaria - South African Journal of Military Studies, 2012)
As long ago as 1700, when the Cape of Good Hope was still a small settlement ruled by the Dutch East India Company, Coloureds were subject to the same military duties as Europeans. It was, however, a foreign war that caused the establishment of the first Pandour regiment in 1781. They comprised a force under white officers that fought against the British prior to the occupation of the Cape in 1795. Between the years 1795-1803 the British employed Coloured soldiers; they became known as the Cape Corps after the second British occupation in 1806. During the first period of British rule Coloured soldiers received a weekly pay of sixpence (sterling) to buy tobacco and were entitled to the same rations and drinks as British troops. During the Anglo-Boer War (1899-1902) Coloureds were used on both sides as drivers, servants and scouts.